A BRIEF REVIEW ON SECONDARY METABOLITES BIOSYNTHESIS REGULATION: APPLICATION IN GYNURA PROCUMBENS IN GLASSHOUSE CONDITION - M.B., Mohamad Fhaizal; Z.E.J., Hawa; G., Ali (Malaysian Journal of Science, 2018)
Secondary metabolites biosynthesis regulation study of herbal plants plays a significant role in the discovery of phytochemical compounds with a wide range of uses. These phytochemical compounds are important nature-derived drugs such as antibiotics, agrochemicals substitutes (allelopathy), pigments, and medicinal immuno-suppressor. Generally, there is a firm scheme for regulating secondary metabolites based on their components, function and synthesis: alkaloids, enzyme, fatty acid, phenolic, polyketides, polypeptides, steroids, and terpenoids. Therefore, with the increasing in economic importance of these valuable compounds has led to a great interest in secondary metabolism, mainly the possibility of modifying and regulating the production of metabolites by means of biotechnological and agricultural practice. This review presents information about the production regulation of bioactive compounds under various stress conditions, particularly on abiotic influence such as water supply and fertilizer application that could be included in G. procumbens production systems. Brief analysis was done by reviewing various collected works and material from articles in related issues. Therefore, it will permit quantitative comparison of studies to address intended questions based on procedures, study systems, locations and scale of used. Keywords: Biosynthesis, glasshouse, Gynura procumbens, metabolites, nitrogen, potassium, review, water